Shape/phase transitions and shape coexistence in even-even nuclei - Bonatsos, Dennis; Martinou, Andriana; Peroulis, Spyridon; Mertzimekis, Theodoros; Minkov, Nikolay (HNPS Advances in Nuclear Physics, 2024)
Shape/phase transitions have been observed in certain regions of the nuclear chart. Shape coexistence is also known to occur in various regions of the nuclear chart, forming islands. The interrelation between these two concepts is considered in the regions around (N=90, Z=60), (N=60, Z=40), (N=40, Z=34), in which shape coexistence due to proton-induced neutron particle-hole excitations is related to a first-order shape/phase transition from spherical to deformed shapes.